Journal of biomimetics, biomaterials and biomedical engineering. Vol. 52 - Suroto, Heri; Hussain, Nandyala Sooraj (Journal of Biomimetics, Biomaterials and Biomedical Engineering Ser., 2021)
Special topic volume with invited peer-reviewed papers only.